What is the importance of climate research? An innovative web-based approach to assess the influence and reach of climate research programs - Carneiro, Bia; Resce, Giuliano; Läderach, Peter R.D.; Schapendonk, Frans; Pacillo, Grazia (Elsevier, 2022)
This study employs an innovative web-based approach to explore the dynamics of agriculture-focused climate science and changes in attitude towards Climate Smart Agriculture (CSA) and climate change, using the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) as a case study.